Early Neoclassical views on Monopoly: the Cournotian heritage (2020)
In spite of Cournot’s unquestionable influence on contemporary theory, his legacy regarding economic policy and, especially, the regulation of monopolies is mostly unknown. In this paper I explore the several forms of Cournot’s analysis of monopolistic market structures, starting with his theoretical model up to his normative and empirical examination. With the help of little known texts of the author I aim at showing the versatility of his ideas and the richness of his analytical legacy. Against this setup I retrace his influence over three of the most important economists of the end of the XIXth century: Walras, Edgeworth and Marshall. I show that there exists a theoretical representation that constitutes the indisputable reference regarding monopolies that is enriched with normative analyses and leads each one of them to their own specific proposals in regulation and economic policy.